2007
DOI: 10.1590/s0100-879x2007000800006
|View full text |Cite
|
Sign up to set email alerts
|

The use of light-emitting diodes to stimulate mitochondrial function and liver regeneration of partially hepatectomized rats

Abstract: The biostimulating effect of laser radiation has been observed in many areas of Medicine. However, there are still several questions to be answered, among them the importance of light coherence in the stimulatory process. In the present study, we used light-emitting diodes (LED) to promote the stimulation of liver regeneration after partial hepatectomy in rats. Fourteen male Wistar rats weighing 200-250 g were submitted to partial hepatectomy (70%) followed by LED light irradiation (630 nm) of the remaining pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…In the present study we assessed hepatic mitochondrial function and MDA levels in intact livers in response to the use of laser as a source of light in a simulation of laser therapy at two different wavelengths applied separately or in combination, based on the basic understanding of some fundamental elements of the interaction between light and matter 1,6 . The main objective was to determine the effect of laser light on hepatic energy capacity based on previous studies from our laboratory about hepatic function and mitochondrial function 5,18,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study we assessed hepatic mitochondrial function and MDA levels in intact livers in response to the use of laser as a source of light in a simulation of laser therapy at two different wavelengths applied separately or in combination, based on the basic understanding of some fundamental elements of the interaction between light and matter 1,6 . The main objective was to determine the effect of laser light on hepatic energy capacity based on previous studies from our laboratory about hepatic function and mitochondrial function 5,18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown an effective interaction between light and biological tissues, the liver in particular [1][2][3][4][5] .Conventional light, as well as light-emitting diodes (LED) and laser, with their different optical properties concerning light production and delivery have similar effects on cell organelles, leading to increased efficiency of wound healing, of hepatocellular mitochondrial energy capacity, and of hepatic regeneration 2,[3][4][5][6] . The partial loss of hepatic tissue rapidly triggers the regenerative process until the original weight is recovered 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…[19] Monochromatic radiation in the visible and infrared A (IRA) range sustains matrix metalloproteinase (MMP), improves mitochondrial function, and increases adenosine triphosphate (ATP) synthesis and O 2 consumption, which leads to cellular regenerative pathways. [20][21][22] We have reported that the mitochondrial-related signalling pathway is responsible for biological effects induced by He-Ne laser in pigmented cells. More specifically, He-Ne irradiation immediately induced an increase in mitochondrial membrane potential, ATP and cyclic adenosine monophosphate (cAMP), as well as JNK/AP1 activity via enhanced cytochrome c oxidase activity in A2058 melanoma cells.…”
Section: Low-energy LI G Hts Irr Ad Iati On and Mitochondrial-rel Amentioning
confidence: 99%
“…The solid-state lighting holds tremendous prospective for future illumination, backlight panel display industry and biomedical applications due to their brightness and durability [1-3]. Over the past decade, much attention has been drawn towards white-light-emitting diodes (WLEDs) as new light sources due to their reliability with great economic and ecological consequences.…”
Section: Introductionmentioning
confidence: 99%